Green Synthesis, Structural, In Vitro and In Vivo Bioactivity Properties of ZnO Nanoparticles for Biomedical Applications - Ibrahim, Essam H.; Albulym, Obaid; Kaygili, Omer; Kilany, Mona; Shkir, Mohd; Hussien, Mai S. A.; Yahia, I. S. (Amer Scientific Publishers, 2019)
Owing to the fascinating applications of ZnO in modern devices, it is interesting to explore its more aspects for future devices. Hence, herein, we have synthesized the high purity spherical ZnO nanoparticles (SNPs) through a facile green synthesis route and robust structural and biomedical studies are carried out. Hexagonal phase with 93.2% crystallinity was confirmed through XRD analysis. ZnO nanoparticles were tested for their bioactivities both in vivo (acute cytotoxicity test) and in vitro (Anti-cancer activities on the liver (HepG2) and cervical (Hela) cancer cell lines, stimulatory/inhibitory effects on normal rat splenic cells, hemolytic effects on red blood cells and antimicrobial activity). Results showed that ZnO SNPs has no cytotoxic effects on the vital organ like the liver and has no hemolytic action on red blood cells. ZnO SNPs showed inhibitory consequence on normal rat splenic cells growth at all tested concentrations. The ZnO nanoparticles showed a stimulatory effect on Hela cell line. Moreover, ZnO nanoparticles showed an inhibitory effect on HepG2 cell line and microbial cells.
Keywords: X-ray Diffraction; Bioactivities; Cytotoxicity Test; Anti-Cancer Activities